Deletion of GOLGA2P3Y but not GOLGA2P2Y is a risk factor for oligozoospermia. Issue 2 (February 2016) - Sen, Sanjukta; Agarwal, Rupesh; Ambulkar, Prafulla; Hinduja, Indira; Zaveri, Kusum; Gokral, Jyotsna; Pal, Asoke; Modi, Deepak
Abstract: The AZFc locus on the human Y chromosome harbours several multicopy genes, some of which are required for spermatogenesis. It is believed that deletion of one or more copies of these genes is a cause of infertility in some men. GOLGA2LY is one of the genes in the AZFc locus and it exists in two copies, GOLGA2P2Y and GOLGA2P3Y . The involvement of GOLGA2LY gene copy deletions in male infertility, however, is unknown. This study aimed to investigate the association of deletions of GOLGA2P2Y and GOLGA2P3Y gene copies with male infertility and with sperm concentration and motility. The frequency of GOLGA2P3Y deletion was significantly higher in oligozoospermic men compared with normozoospermic men (7.7% versus 1.2%; P = 0.0001), whereas the frequency of GOLGA2P2Y deletion was comparable between oligozoospermic and normozoospermic men (10.3% versus 11.3%). The deletion of GOLGA2P3Y but not GOLGA2P2Y was significantly higher ( P = 0.03) in men with gr/gr rearrangements, indicating that GOLGA2P3Y deletions increase the susceptibility of men with gr/gr rearrangements to oligozoospermia. Furthermore, men with GOLGA2P3Y deletion had reduced sperm concentration and motility compared with men without deletion or with deletion of GOLGA2P2Y . These findings indicate GOLGA2P3Y gene copy may be candidate AZFc gene for male infertility.